Peran Dan Tanggung Jawab Negara Dalam Perlindungan Hukum Tenaga Kerja Indonesia Yang Bermasalah Di Luar Negeri - Ida Hanifah (Universitas Muhammadiyah Sumatera Utara, 2020)
Many legal cases and other cases experienced by Indonesian Migrant Workers (TKI) abroad which are detrimental to these migrant workers. Based on these facts, the State should play a role and be fully responsible for the safety and welfare of TKI. The role and responsibility of the state is not only contained in the contents of the law solely, but must be implemented in an effort to protect the law against migrant workers who work abroad. Based on the facts, it turns out that the various regulations related to the protection of TKIs abroad, there is overlap between one institution and another, the other problem is that agreements between the Government of the Republic of Indonesia and the destination countries for migrant workers must be frequently reviewed, due to state regulations objectives often change so that many migrant workers are harmed by the policy